Scheduling Sports Competitions at Multiple Venues: Revisited - LIM, Andrew (Institutional Knowledge at Singapore Management University, 2006)
In this work, we study scheduling sports competitions at multiple venues, a problem recently introduced by Urban and Russell [T.L. Urban, R.A. Russell, Scheduling sports competitions on multiple venues, European Journal of Operational Research 148 (2003) 302–311]. The distinguishing feature of the problem is that venues come into play when scheduling. We develop beam search and simulated annealing approaches to the problem and its extension. Computational experiments were conducted and algorithms compared and analyzed. We found that the simulated annealing algorithm with specialized neighborhood moves achieved superior solutions in significantly shorter times than the method of Urban and Russell.